COVID-19 on the spectrum: a scoping review of hygienic standards - Voidarou, Chrysa; Rozos, Georgios; Stavropoulou, Elisavet; Giorgi, Elpida; Stefanis, Christos; Vakadaris, Georgios; Vaou, Natalia; Tsigalou, Christina; Kourkoutas, Yiannis; Bezirtzoglou, Eugenia (Frontiers in Public Health, 2023)
The emergence of Covid-19 in Wuhan, China, rapidly escalated into a worldwide public health crisis. Despite numerous clinical treatment endeavours, initial defences against the virus primarily relied on hygiene practices like mask-wearing, meticulous hand hygiene (using soap or antiseptic solutions), and maintaining social distancing. Even with the subsequent advent of vaccines and the commencement of mass vaccination campaigns, these hygiene measures persistently remain in effect, aiming to curb virus transmission until the achievement of herd immunity. In this scoping review, we delve into the effectiveness of these measures and the diverse transmission pathways, focusing on the intricate interplay within the food network. Furthermore, we explore the virus's pathophysiology, considering its survival on droplets of varying sizes, each endowed with distinct aerodynamic attributes that influence disease dispersion dynamics. While respiratory transmission remains the predominant route, the potential for oral-faecal transmission should not be disregarded, given the protracted presence of viral RNA in patients' faeces after the infection period. Addressing concerns about food as a potential viral vector, uncertainties shroud the virus's survivability and potential to contaminate consumers indirectly. Hence, a meticulous and comprehensive hygienic strategy remains paramount in our collective efforts to combat this pandemic.